Novel pyrazole bearing heterocyclic hybrids as promising biologically active compounds - Shabelnyk, K. P.; Zaika, Ye.; Skoryna, D. Yu.; Nosulenko, I. S.; Kinichenko, A. O.; Voskoboinik, O.; Kovalenko, S.; Шабельник, Костянтин Петрович; Скорина, Дмитро Юрійович; Носуленко, Інна Степанівна; Кініченко, Анна Олександрівна (My University, 2024)
The paper presents the results of a study devoted to the synthesis, evaluation of physicochemical properties, antiradical, and antimicrobial activity of pyrazole-containing heterocyclic hybrids. It has been shown that pyrazole bearing heterocyclic hybrids that contain quinazoline, triazoloquinazoline or triazole moieties are available via a series of reactions that include the interaction of 4-chloroquinazoline with pyrazole-containing hydrazides, cyclization of formed products into corresponding triazoloquinazolines, and hydrolytic cleavage of the electron-deficient tricyclic system. The structures of synthesized compounds have been verified by a complex of physicochemical methods, and the features of 1H NMR spectral characteristics have been described as well. The evaluation of obtained compounds’ biological activity revealed a moderate bacteriostatic effect against Pseudomonas aeruginosa and Candida albicans, as well as high radical scavenging activity of some of the studied heterocyclic hybrids.
Keywords: heterocyclic hybrids; pyrazole; quinazoline; triazole; antiradical activity